GE_GERICHTE C/11520/2012 vom 19. November 2013 - GE Cour de justice (2013)
LOYER INITIAL; FORMULE OFFICIELLE; LOYER FONDÉ SUR LES PRIX DU MARCHÉ; RÉPÉTITION(ENRICHISSEMENT ILLÉGITIME) | CPC.311; CO.269; CO.269d; CO.270.2; CO.63.1; LaCC.22.1